PENGARUH RASIO KEUANGAN TOTAL ASSETS TURNOVER NET PROFIT MARGIN DAN RETURN ON ASSETS TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Iin Nur Afifah; Syafrudin Arif Marah Manunggal (Jurnal Ilmiah Global Education, 2023)
Developments in the world in the economic field in the Indonesian and international regions have greatly encouraged a lot of competition for business people who are passionate about competing. This study aims to measure the profit growth of manufacturing companies that will be sampled. The variables used are the dependent and independent variables, while the dependent variable is profit growth. The independent variables include the financial ratios of trun on assets, Net Provit Margin and Return on Assets. This study uses panel data regression model testing with several tests. The results of the analysis show that partially the financial ratios of total assets turnover and return on assets have an effect on profit growth while the financial ratios of net profit margin have no effect on profit growth in manufacturing companies listed on the Indonesian stock exchange. Then the data used in this study as many as 20 companies have fulfilled the classic assumptions which include normally distributed data, no multicollinearity symptoms occur, there are problems with heteroscedasticity symptoms. The results of this study can provide information for the public or investors by choosing high quality companies by looking at profit growth and corporate financial statements